The Discrepancy between Knowledge and Competency of Independent Smallholder Farmer’s - Nurliza Nurliza; Eva Dolorosa; U Edi Suryadi (Jurnal Penyuluhan, 2018)
Recently, independent smallholders faced the crucial challenges of  certification requirements, i.e. The lack of farmers’ organization, the cost barrier; doesn't possess the mandatory legal documents; don't use appropriate best practices or keep records; and lack of skill and knowledge. Therefore, the understanding of the discrepancy between knowledge and competence was urged to overcome the critical issues in certification for achieving the sustainable development of palm oil production. The analyzed data using in-depth interviews of 150 respondents that is structured base for Indonesian sustainable palm oil (ISPO) with non-hierarchical clustering methods. The result proved that the largest discrepancy between knowledge and competence level was sustainable business improvement aspect, while, farmers’ organization and farm management aspect were the smallest in overall clusters. Thus, an affordable information intervention, extension and target groups through the required motivation for self-improvement and evaluate the pattern of information for  minimizing the gaps.